2012
DOI: 10.6028/nist.tn.1753
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Enterprise / Technical Data Package Summit Report

Abstract: This report summarizes the presentations, discussions and recommendations from the Model-Based Enterprise Summit held at the National Institute of Standards and Technology in December of 2011. The purpose of the Summit was to identify challenges, research, implementation issues, and lessons learned in manufacturing and quality assurance where a digital three-dimensional (3D) model of the product serves as the authoritative information source for all activities in the product's lifecycle. The report includes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…Furthermore, the exact procedures, associated implementation costs, and practical steps that can lead companies to these savings need to be formally established. Nevertheless, the adoption of MBE practices has become a reality in industry, as shown by the increasing number of companies that are transitioning to model-based paperless environments [26]. In this paper, we focus on the proper communication of design information within MBE environments.…”
Section: Model-based Enterprise (Mbe)mentioning
confidence: 99%
“…Furthermore, the exact procedures, associated implementation costs, and practical steps that can lead companies to these savings need to be formally established. Nevertheless, the adoption of MBE practices has become a reality in industry, as shown by the increasing number of companies that are transitioning to model-based paperless environments [26]. In this paper, we focus on the proper communication of design information within MBE environments.…”
Section: Model-based Enterprise (Mbe)mentioning
confidence: 99%
“…It is important that manufacturability information given to them should be in a language understandable to them. Many manufacturing and architecture industries still make use of traditional paper and 2D engineering drawings to convey design intent (Gott, 2003;Lubell, Chen, Horst, Frechette, & Huang, 2012;Opsahl, 2013). Studies have shown that modality of information affects performance and workload of humans (Cao, Theune, & Nijholt, 2009;Tavanti & Lind, 2001;Kashihara, 2009;Gîrbacia, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this paradigm, CAD models become the central point around which all engineering processes revolve. MBE provides practical opportunities for efficiency and effectiveness in product development, particularly in the area of reusability [Lubell et al, 2012].…”
Section: Contextmentioning
confidence: 99%
“…The Model-Based Engineering (MBE) paradigm is an approach to product development that uses CAD models rather than documents as the data source for all engineering activities throughout the product life cycle. The core idea is that models can be used to drive all aspects of the product lifecycle and data is created once and reused by all downstream stakeholders [Lubell et al, 2012]. This means that all the required engineering information is communicated to everyone from one source, the digital model.…”
Section: Model-based Engineering (Mbe)mentioning
confidence: 99%
See 1 more Smart Citation